Blue box. Volume 9 - Miura, Kouji (Manga author) (Miura, Kouji (Manga author). Ao no hako., 2024)
"The joint training camp has begun, and Taiki must endure even tougher practices than usual. But all he can think about are Chinatsu and Hina! During the final night of the camp, Taiki finds himself alone with Hina once again and realizes he needs to be more honest with himself--and with her"--